(untitled) (Orinoquia, 2021)
The social manifestations that show gender inequality, are present in all areas of human activity, are more visible in those rural environments, where indigenous settlements survive, whose social relations with other cultures are marked by gender imaginations that are They express precisely, in the setting of this research, carried out during 2017, atthe Trietnica Yaaliakeisy Educational Institution of the Municipality of Puerto López, department of Meta, a pedagogical environment where members of the peasant community and the Achagua, Sikuani, ethnic groups coexist. Piapoco and Kubeo. The research objective is to identify the gender manifestations of teachers and students of this institution, to address the knowledge of how expressions that demonstrate the existence of social imaginaries related to the roles of women and men are communicated. In methodological terms, the qualitative ethnographic approach was chosen, applying direct observation techniques, information gathering through semi-structured interviews and field work with focus groups; systematization of the information through the categorization and subcategorization of the data and its examination with the content analysis methodology. The results of the research show that there are gender roles through which themembers of this community perceive the condition of women as fragility and that of men as power. It is concluded that in this scenario the conditions of inequality are maintained that, due to nurtured traditions, from ethnic cultural expressions, privilege the roles of the masculine over thefeminine. Faced with this panorama, it is necessary to sensitize the communities by transforming thoughts of submission and domination, into imaginary where representations of equality between genders persist, ensuring that the new generations, in these communities, train their daughters and sons with human values based on gender equality.